2015
DOI: 10.1080/09168451.2014.972326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes encoding photoconvertible (Class I) water-soluble chlorophyll-binding proteins from Chenopodium ficifolium

Abstract: Photoconvertible water-soluble chlorophyll-binding proteins, called Class I WSCPs, have been detected in Chenopodiaceae, Amaranthaceae and Polygonaceae plant species. To date, Chenopodium album WSCP (CaWSCP) is the only cloned gene encoding a Class I WSCP. In this study, we identified two cDNAs encoding Chenopodium ficifolium Class I WSCPs, CfWSCP1, and CfWSCP2. Sequence analyses revealed that the open reading frames of CfWSCP1 and CfWSCP2 were 585 and 588 bp, respectively. Furthermore, both CfWSCPs contain cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Subsequently, similar photoconvertible WSCPs were isolated from various plants of Chenopodiaceae, Amaranthaceae and Polygonaceae (Takamiya ; Takahashi et al . ). In addition to these photoconvertible WSCPs, Murata et al .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Subsequently, similar photoconvertible WSCPs were isolated from various plants of Chenopodiaceae, Amaranthaceae and Polygonaceae (Takamiya ; Takahashi et al . ). In addition to these photoconvertible WSCPs, Murata et al .…”
Section: Introductionmentioning
confidence: 97%
“…Class I WSCPs are members of the Domain Unknown Function (DUF) 538 superfamily (Takahashi et al . , ), while Class II WSCPs are members of the Kunitz‐type trypsin inhibitor family (Satoh et al . ; Bektas et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2−4) Based on their photoconvertibility, WSCPs can be categorized into two classes, Class I (photoconvertible type) and Class II (non-photoconvertible type). 1) Sequence analyses revealed that Chenopodium album WSCP (CaWSCP), a Class I WSCP, is a member of the domain unknown function 538 superfamily 5,6) while all Class II WSCPs belong to the Kunitz-type trypsin inhibitor family. 1,3,7−10) There have been various studies on the biochemical and physicochemical properties of Class I WSCPs, including CaWSCP.…”
mentioning
confidence: 99%